Sapphire blue - Gier, Kerstin (Gier, Kerstin. Liebe geht durch alle Zeiten., 2012)
Sixteen-year-old Gwen, the newest and final member of the secret time-traveling Circle of Twelve, searches through history for the other time-travelers, aided by friend Lesley, James the ghost, Xemerius the gargoyle demon, and Gideon, the Diamond, whose fate seems bound with hers.